2019
DOI: 10.3390/f10080624
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Phenolic Compounds and Antioxidant Activity in Leaves of Cyclocarya paliurus (Batal.) Iljinskaja

Abstract: Cyclocarya paliurus (Batal.) Iljinskaja is a plant with nutraceutical importance since its leaves have been used historically as folk medicines for hundreds of years. The content of 10 phenolic compounds was determined throughout the growing season by high-performance liquid chromatography (HPLC) with UV detector, while the antioxidant activities of C. paliurus leaf extracts were evaluated by 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt radical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…Our result is in accordance with the recent reports, which suggested that higher phenolic content exhibited stronger antioxidant activity. A similar linear correlation was also reported in Moringa oleifera, Cyclocarya paliurus leaves, Juglans sigillata husk, Ocimum basilicum leaves, and Juglans regia [17,[28][29][30][31]. Moreover, the correlation coefficient between phenolic compounds and total antioxidant activity in CUPRAC and DPPH assay (r 2 > 0.91, p < 0.05) is stronger than that of antioxidant activity in FRAP assay (r 2 < 0.80, p < 0.05).…”
Section: Correlation Between Contents Of Phenolic Compounds and Antioxidant Activitysupporting
confidence: 82%
“…Our result is in accordance with the recent reports, which suggested that higher phenolic content exhibited stronger antioxidant activity. A similar linear correlation was also reported in Moringa oleifera, Cyclocarya paliurus leaves, Juglans sigillata husk, Ocimum basilicum leaves, and Juglans regia [17,[28][29][30][31]. Moreover, the correlation coefficient between phenolic compounds and total antioxidant activity in CUPRAC and DPPH assay (r 2 > 0.91, p < 0.05) is stronger than that of antioxidant activity in FRAP assay (r 2 < 0.80, p < 0.05).…”
Section: Correlation Between Contents Of Phenolic Compounds and Antioxidant Activitysupporting
confidence: 82%
“…The levels of secondary metabolites in plants can vary depending on the environmental conditions and the stage of development of the plant [ 51 ]. Phenolic compounds, which are one of the main groups of secondary metabolites, are not an exception.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both the hosts and P . capitata are under favorable photosynthetic conditions (sunshine, abundance of minerals, and water) [ 51 ], boosting the rate of secondary metabolite biosynthesis in these plants [ 52 ]. At the same time, in this study, the rate of production of total tannins decreased from the vegetative phase to the fruiting stage, certainly passing to flowers.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the fruits we noticed only small changes in the "Cingapura" and "Uthirankota" cultivars (Figure 4B). According to the literature, these variations can be occasioned by several factors, biotic and abiotic, such as plant defense, senescence, plant development, and interactions with the environment in which they are inserted [84]. The levels of total phenolics were higher in the leaves in comparison to the fruits.…”
Section: Total Phenolics Determinationmentioning
confidence: 99%